Mediated and Marginalised: Translations of Modern and Contemporary Chinese Literature in Spain (1949-2010) - Marin-Lacarta, Maialen (Meta, 2018)
The history and reception of translations of modern and contemporary Chinese literature in Spain form the basis of the discussion in this article. Eighty-four translations of modern and contemporary Chinese literature were published in Spain – either in Spanish or in Catalan – between 1949 and 2010. Using this under-researched corpus as a starting-point, this article explores two interrelated premises: the marginalisation of modern and contemporary Chinese literature in Spain and the mediation of its Spanish reception by Anglophone and Francophone literary systems. To do so, the study investigates the history of translations, pays attention to the evolution of types of translation (direct and indirect), and uses concrete examples from paratexts (back covers and prefaces) and translation reviews. After a discussion of the predominance of indirect translations, three recurring motifs inferred from an analysis of the paratexts and reviews are presented: (a) a preference for documentary value, (b) an insistence on difference and (c) an emphasis on politics and trauma (censorship, dissidence and the Cultural Revolution). In addition, I demonstrate the connections between these recurring motifs in the Spanish reception of Chinese literature in relation to European orientalism and area studies. Ultimately, the recent history of translations of modern and contemporary Chinese literature in Spain helps us to reflect on the complexity and hierarchical nature of literary exchanges on a global scale.